The mitochondrial genome of the land snail Camaenella platyodon (Pfeiffer, 1846) (Stylommatophora, Camaenidae). Issue 2 (3rd July 2019) - Hu, Mei-Ling; Wang, Pei; Chen, Yu; Zhang, Ming-Zhe; Yang, Ping-Shan; Lin, Jun-Hong; Zhou, Wei-Chuan
Abstract: The complete mitochondrial genome (mitogenome) of Chinese endemic snail Camaenella platyodon (Pfeiffer, 1846) has been sequenced and annotated in this study. The entire circular genome is 13, 985 bp in size and represents the third camaenid mt genome, with 2 ribosomal RNA genes, 22 transfer RNA genes, 13 protein-coding genes. All of genes are divided into two groups, including 24 genes on the majority coding strand (J strand) and others on the minority coding strand (N strand). Phylogenetic analysis of 13 protein-coding genes suggests that C . platyodon is closely related to the species in family Camaenidae.